2017
DOI: 10.1111/iej.12782
|View full text |Cite
|
Sign up to set email alerts
|

The roles of autophagy and hypoxia in human inflammatory periapical lesions

Abstract: Huang HY, Wang WC, Lin PY, Huang CP, Chen CY, Chen YK. The roles of autophagy and hypoxia in human inflammatory periapical lesions. International Endodontic Journal, 51, e125-e145, 2018. Aim To determine the expressions of hypoxia-related [hypoxia-inducible transcription factors (HIF)-1a, BCL2/adenovirus E1B 19 kDa protein-interacting protein 3 (BNIP3) and phospho-adenosine monophosphate activated protein kinase (pAMPK)] and autophagy-related [microtubule-associated protein 1 light chain 3 (LC3), beclin-1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 44 publications
0
44
0
6
Order By: Relevance
“…After stably and rapidly accumulating in the nucleus under hypoxic conditions, HIF-1α binds with HIF-1β to activate the HIF-1 heterodimeric complex, which promotes the expression of hypoxia target genes through combining with the hypoxia response element (33,36,37). Studies have revealed that the associations between hypoxia and autophagy are mainly through HIF-1regulated expression of downstream target proteins BNIP3 and BNIP3L, which release Beclin1 to activate autophagy by disrupting the interaction between Beclin1 and Bcl-2/Bcl-xL complexes (33,(38)(39)(40). Another study has suggested that hypoxia-induced cancer cell autophagy was an HIF-1 independent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…After stably and rapidly accumulating in the nucleus under hypoxic conditions, HIF-1α binds with HIF-1β to activate the HIF-1 heterodimeric complex, which promotes the expression of hypoxia target genes through combining with the hypoxia response element (33,36,37). Studies have revealed that the associations between hypoxia and autophagy are mainly through HIF-1regulated expression of downstream target proteins BNIP3 and BNIP3L, which release Beclin1 to activate autophagy by disrupting the interaction between Beclin1 and Bcl-2/Bcl-xL complexes (33,(38)(39)(40). Another study has suggested that hypoxia-induced cancer cell autophagy was an HIF-1 independent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…As an essential regulator in hypoxia-induced bone development, Hypoxia-induced factor-1 alpha (HIF-1) has an important role in chondrogenesis and osteogenesis [87]. Huang et al investigated HIF-1, BNIP3, pAMPK, and autophagy-related proteins (LC3, beclin-1, Atg5-12, and p62) in human infl ammatory periapical lesions [88]. They evaluated samples from patients with radicular cysts (RCs), Periapical Granulomas (PGs) and healthy dental pulp tissues.…”
Section: Hypoxia and Autophagymentioning
confidence: 99%
“…They evaluated samples from patients with radicular cysts (RCs), Periapical Granulomas (PGs) and healthy dental pulp tissues. After immunohistochemical analysis, the expression of autophagy and hypoxia-related proteins in each group were compared with each other [88]. In periapical lesions, HIF-1, Bnip3, pAMPK, LC3II, and Atg5-12 proteins were signifi cantly higher than those in healthy dental pulp tissues [88].…”
Section: Hypoxia and Autophagymentioning
confidence: 99%
“…Compared to normal tissues, autophagic activity significantly increases in periapical lesions (Huang et al . ). More interestingly, studies also revealed the existence of an interplay between autophagy and apoptosis in the pathogenesis of apical periodontitis (Lai et al .…”
Section: Introductionmentioning
confidence: 97%